2007
DOI: 10.1002/ana.21161
|View full text |Cite
|
Sign up to set email alerts
|

Congenital lymphocytic choriomeningitis virus infection: spectrum of disease

Abstract: Congenital LCMV infection can have diverse presenting signs, neuroimaging abnormalities, and clinical outcomes. In the companion article to this study, we utilize an animal model to show that the clinical and pathological diversity in congenital LCMV infection is likely due to differences in the gestational timing of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 39 publications
(59 reference statements)
3
131
0
Order By: Relevance
“…LCMV infection in a pregnant woman can spread to the fetus, resulting in abortion early in pregnancy (Deibel et al, 1975) or malformations, including hydrocephalus, intracranial calcifications, and chorioretinitis if the infection occurs later in pregnancy (Ackermann et al, 1974;Sheinbergas, 1975;Barton et al, 1993Barton et al, , 1996Wright et al, 1997;Marrie and Saron, 1998;Barton and Hyndman, 2000;Jamieson et al, 2006;Bonthius et al, 2007b). A study by Bonthius and colleagues (2007b) reports on 20 children with serologically confirmed congenital LCMV infection who were followed for up to 11 years.…”
Section: Lcmv Infection In Pregnancymentioning
confidence: 99%
“…LCMV infection in a pregnant woman can spread to the fetus, resulting in abortion early in pregnancy (Deibel et al, 1975) or malformations, including hydrocephalus, intracranial calcifications, and chorioretinitis if the infection occurs later in pregnancy (Ackermann et al, 1974;Sheinbergas, 1975;Barton et al, 1993Barton et al, , 1996Wright et al, 1997;Marrie and Saron, 1998;Barton and Hyndman, 2000;Jamieson et al, 2006;Bonthius et al, 2007b). A study by Bonthius and colleagues (2007b) reports on 20 children with serologically confirmed congenital LCMV infection who were followed for up to 11 years.…”
Section: Lcmv Infection In Pregnancymentioning
confidence: 99%
“…Congenital infection may lead to spontaneous abortion (Bonthius et al, 2007), and previously documented cases of transplant-associated infections of immunocompromised individuals showed fatal outcomes in most patients (Fischer et al, 2006;CDC, 2008;Palacios et al, 2008;MacNeil et al, 2012;Schafer et al, 2014). In the case of congenital infection, the virus may not be detected aft er the infant is born, but specifi c IgGs are present in the mother's and infant's sera.…”
Section: Discussionmentioning
confidence: 97%
“…In immunocompetent adults, infections are mostly asymptomatic or mild, with fl u-like symptoms, but diseases of the CNS, such as aseptic meningitis, can also occur (Barton and Mets, 2001). In contrast to the self-limited acquired postnatal LCMV infection, prenatal infection leads to an increased risk of spontaneous abortion, severe CNS defects (hydrocephalus, microcephaly), and chorioretinitis of the foetus (Bonthius et al, 2007). Moreover, recently reported transmissions of LCMV through infected solid organ transplants revealed a risk to immunocompromised individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-to-human transmission has been documented through organ donation associated with severe disease in the immunocompromised recipient (Fischer et al, 2006), and congenital infections leading to severe and irreversible brain (Barton et al, 1993;Barton and Mets, 2001;Bonthius et al, 2007;Wright et al, 0166-0934/$ -see front matter © 2011 Elsevier B.V. All rights reserved. doi:10.1016/j.jviromet.2011.06.018 1997) and retinal (Bonthius et al, 2007;Mets et al, 2000) injury have been described.…”
Section: Introductionmentioning
confidence: 99%